A multiproxy record of sedimentation, pedogenesis, and environmental history in the north of West Siberia during the late Pleistocene based on the Belaya Gora section. Issue 1 (January 2021) - Sheinkman, Vladimir; Sedov, Sergey; Shumilovskikh, Lyudmila S.; Bezrukova, Elena; Dobrynin, Dmitriy; Timireva, Svetlana; Rusakov, Alexey; Maksimov, Fedor
Abstract: Recent revision of the Pleistocene glaciation boundaries in northern Eurasia has encouraged the search for nonglacial geological records of the environmental history of northern West Siberia. We studied an alluvial paleosol-sedimentary sequence of the high terrace of the Vakh River (middle Ob basin) to extract the indicators of environmental change since Marine Oxygen Isotope Stage (MIS) 6. Two levels of the buried paleosols are attributed to MIS 5 and MIS 3, as evidenced by U/Th and radiocarbon dates. Palynological and pedogenetic characteristics of the lower pedocomplex recorded the climate fluctuations during MIS 5, from the Picea-Larix taiga environment during MIS 5e to the establishment of the tundra-steppe environment due to the cooling of MIS 5d or MIS 5b and partial recovery of boreal forests with Picea and Pinus in MIS 5c or MIS 5a. The upper paleosol level shows signs of cryogenic hydromorphic pedogenesis corresponding to the tundra landscape, with permafrost during MIS 3. Boulders incorporated in a laminated alluvial deposit between the paleosols are dropstones brought from the Enisei valley by ice rafting during the cold MIS 4. An abundance of eolian morphostructures on quartz grains from the sediments that overly the upper paleosol suggests a cold, dry, and windy environment during the MIS 2 cryochron.